2013
DOI: 10.1051/0004-6361/201219600
|View full text |Cite
|
Sign up to set email alerts
|

Long quasi-periodic oscillations of sunspots and nearby magnetic structures

Abstract: Aims. Simultaneous study of long quasi-periodic oscillations in sunspots (using line-of-sight magnetic field data) and nearby magnetic structures located above them (using radio emission data at 37 GHz) was the basic aim of this work. Methods. Data from the ground-based radio-telescope (Metsähovi Radio Observatory, Aalto University, Finland) and the Helioseismic and Magnetic Imager instrument on-board the Solar Dynamics Observatory spacecraft were obtained and analyzed. We used the wavelet (Morlet) analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
(46 reference statements)
2
13
0
Order By: Relevance
“…In addition, recovery of four-hour and nine-hour periods in the o1 box (in Figure 3) and the qs1 box (in Figure 5b) lie at the edges of the typical range of periods reported in Telloni et al (2013), but all are well within the range of periods previously recovered for a range of solar coronal structures (e.g. Ivanov, 1983;Foullon, Verwichte, and Nakariakov, 2004;Smirnova et al, 2013;Auchère et al, 2014). Furthermore, the o1 and qs1 detections are both marginally above global confidence levels and rely on the form of the fitted background power derived from Equation 1.…”
Section: Recovery Of Periodic Signaturessupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, recovery of four-hour and nine-hour periods in the o1 box (in Figure 3) and the qs1 box (in Figure 5b) lie at the edges of the typical range of periods reported in Telloni et al (2013), but all are well within the range of periods previously recovered for a range of solar coronal structures (e.g. Ivanov, 1983;Foullon, Verwichte, and Nakariakov, 2004;Smirnova et al, 2013;Auchère et al, 2014). Furthermore, the o1 and qs1 detections are both marginally above global confidence levels and rely on the form of the fitted background power derived from Equation 1.…”
Section: Recovery Of Periodic Signaturessupporting
confidence: 74%
“…The Solar Dynamics Observatory (SDO: Pesnell, Thompson, and Chamberlin, 2012) allows for continuous high-resolution and high-cadence measurements across a suite of instruments; this observatory has also contributed significantly to studies of long-period oscillatory features in recent years. Examples include Smirnova et al (2013), who uncovered evidence of threeto seven-hour oscillatory periods using the Heliospheric and Magnetic Imager (HMI: Scherrer et al, 2012) onboard SDO, while Froment et al (2015) found four-to nine-hour periodic signatures using the Atmospheric Imaging Assembly (AIA: Lemen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Data on the sunspot magnetic field were provided by the Solar Dynamics Observatory (SDO). The results of similar studies were reported in (Smirnova et al, 2013), where the presence of slow quasi periodic oscillations of the radio emission of near sunspot and intersunspot radio sources and oscillations of the magnetic field strength of photospheric sunspots with equal periods falling within the interval of 200-400 min was demonstrated. It was also noted that temporal variations in the series of radio emission were delayed with respect to the cor responding variations of the magnetic field strength of the closest spot, and the delay time was 15-35 min.…”
Section: Introductionsupporting
confidence: 77%
“…These long-period oscillations were found to be relatively stable and were suggested to be interpreted as a radial mode of sunspot oscillations. Even longer periods of 200 -400 min were found in a later work (Smirnova et al, 2013b).…”
Section: Long-period Oscillationsmentioning
confidence: 80%